A Latent Profile Analysis of Affective Triggers for Risky and Impulsive Behavior - Kemp, Emily; Sadeh, Naomi; Baskin-Sommers, Arielle (Frontiers in Psychology, 2019)
Common theoretical models of risky and impulsive behaviors suggest that individuals engage in risky behavior to avoid negative affect or enhance positive affect. However, little research has been done to identify person-centered affective profiles of risky and impulsive behavior, and delineate the individual differences across these profiles. The present study used the Risky, Impulsive, and Self-destructive Behavior Questionnaire in community [N = 439] and incarcerated [N = 262] samples to examine latent affect profiles for risky and impulsive behavior. Four affective profiles emerged: low avoidance and low approach, average avoidance and average approach, high avoidance, and high approach. Conditional probability correlations revealed meaningful differences across these profiles in psychiatric symptomatology, personality characteristics, and behavior. Consideration of affective triggers provides an important framework for dissociating the underlying reasons why individuals engage in risky behavior.